Peyronie’s disease - a condition affecting many - Łoś, Dawid; Nowak, Aleksandra; Janus, Anita; Kaptur, Agata; Dziedziński, Dawid (Quality in Sport, 2024)
Introduction Peyronie’s Disease (PD) is an acquired connective tissue disorder resulting in abnormal healing of the tunica albuginea causing abnormal curvature, narrowing and shortening of the penis, can also lead to difficulties in coitus. In affecting up to 13% of the adult male population, it can also be a major psychological issue, therefore many of existing therapeutic options are worth looking into. This article provides a review of current knowledge about etiology and ways of treatment as well as a closer look into the impact on mental health among males affected with PD Review methods English-language scientific literature found in PubMed was used for the review. Articles were searched based on keywords. Each article was analyzed for knowledge currency and relevance for use in the review. Description of the State of Knowledge After searching the articles, 32 articles were selected for final analysis. The collected data provided the latest information on Peyronie’s disease while showing the connection between Peyronie’s disease and overexpression of HLA-B7 antigen, TGF-β1, anti DNA, antinuclear and anti elastin antibodies. The treatment could be non-invasive, intralesional or surgical. Summary Peyronie’s disease is a condition that requires a holistic approach with physical difficulties being as important as a patient’s mental health.